PENGARUH RASIONALITAS PENGGUNAAN ANTIHIPERTENSI DENGAN STANDART GUIDELINE JNC 8 TERHADAP KEBERHASILAN TERAPI HIPERTENSI DI RS PANTI WALUYO SURAKARTA - Dian Anggraini, Truly; Wisnu Kusuma, Eka; Diandari, Deswinda (Jurnal Farmasi (Journal of Pharmacy), 2017)
Hypertension is one of the main problems of public health in the whole world and a factor tersering the risks of cardiovascular diseases .The prevalence of hypertension in the population of 18 years and older age of 29,8 % .An epidemiological data shows that a rise in blood pressure will increase the cardiovascular diseases, must be treated with proper and hypertension. The study aimed to identify the influence of rationality use of antihypertensives to the standard guideline jnc 8 to successful therapy hypertension in the hospital at waluyo surakarta year 2016 . The research is research cohort where over the withdrawal of funds data was undertaken in the manner of a retrospective from the records of record medical exam patients hypertension as an in patient in the year 2016 .After the recent retrieval of so sample will be analyzed the usage patterns antihypertensive drug as well as rationality the use of antihypertensive drug with a standard guideline jnc 8 have been analyzed in the manner of a diskriptif, the influence of rationality the use of antihypertensive drug with a standard guideline jnc 8 to successful ( therapy the point of view of achieve the target of the pressure of the blood patients ) have been analyzed is statistically use chi-square. The results of the study , 84 patients get therapy hypertension that is rational in accordance with guideline jnc 8 and 16 patients get therapy hypertension that is irrational with guideline jnc 8. The pattern of an antihypertensive drug, 52 patients prescribed an antihypertensive drug only begotten or unique son, 43 patients a combination 2 an antihypertensive dru , this is more than the patients prescribed more than 2 antihypertensive drug .The success of thera, 65 the patient from 84 cases of patients who get therapy hypertension that is rational managed to reach the target the pressure of the blood and he received treatment therapy assessed as being successful. A significant relation exists between rationality therapy hypertension with guideline jnc 8 against ketercapaian the success of therapy ( p<0,05 ).